(Trans)Forming pictures: an exploration of trans* diversity within Mar C. Llop’s work Identity Constructions - Lorena González-Ruiz (e-cadernos ces)
This article explores the work of trans* activist and photographer Mar C. Llop “Identity Constructions, Work in progress” (2017) from the perspective of contemporary Catalan critical trans studies, specifically, using trans* activist and researcher Miquel Missé’s criticism of the biomedical paradigm within contemporary trans body ethics (Missé, 2018). Drawing from historical conceptualizations of trans* identities in Barcelona and conducting a documental analysis to set a dialogue between Llop’s photographies and Missé’s arguments, this article aims at widening our current epistemological framework on trans* and other gender-dissident identities through organic materiality, practice, and experience, ultimately giving voice while producing multiple embodied queer epistemologies (Santos, 2023).